Comparison of a polymerase chain reaction assay and a conventional microbiologic method for detection of methicillin-resistant Staphylococcus aureus. - Tokue, Y (1992)
The presence or absence of a methicillin resistance gene in 58 clinical isolates of Staphylococcus aureus was examined by the polymerase chain reaction (PCR) and Southern blot analyses. The results were analyzed in relation to those of the MIC assay of methicillin and oxacillin. PCR assay results were identical to those of Southern blot analysis of genomic DNA digested with HindIII (positive, 28 strains; negative, 30 strains). Among the 28 PCR-positive strains, 6 strains showed methicillin susceptibility by the conventional susceptibility test (MICs, less than or equal to 8 micrograms/ml). Culturing of the six strains with ceftizoxime led to an increase in the phenotypic level of resistance to methicillin and oxacillin, indicating that these strains should be classified as methicillin-resistant S. aureus (MRSA). The PCR assay was found to be a sensitive and reliable procedure for the rapid diagnosis of MRSA infection, even in cases in which the conventional MIC assay failed to detect MRSA.